Facile synthesis of MoS2/reduced graphene oxide composites for efficient removal of Cr(vi) from aqueous solutions. Issue 39 (3rd May 2017) - Jiang, Xiaolu; Luo, Hanjin; Yin, Yuwei; Zhou, Weijia
Abstract : Cr(vi ) as a common heavy metal contaminate has attracted much attention for its high toxicity and bioaccumulation. Abstract : Cr(vi ) as a common heavy metal contaminate has attracted much attention for its high toxicity and bioaccumulation. In this study, novel adsorbents, MoS2 /reduced graphene oxide composites (MoS2 /rGO), were prepared via a facile solvothermal process and effectively used for Cr(vi ) adsorption. The MoS2 /rGO was characterized by SEM, TEM, XRD, BET and XPS. Results showed that the MoS2 layers had been successfully grown on the surface of reduced graphene oxide layers. MoS2 /rGO exhibited an enhanced surface area of 81.34 m 2 g −1, more than rGO (57.20 m 2 g −1 ) and MoS2 (1.57 m 2 g −1 ). Batch adsorption experiments of Cr(vi ) were also investigated. The pseudo-second order model best described the adsorption kinetics. Effective Cr(vi ) removal occurred in a wide pH range from 2.0 to 10.0. The excellent adsorption capacity at 25 °C, calculated from the Langmuir isotherm model, was 268.82 mg g −1 at pH 2.0 and 192.63 mg g −1 at pH 4.6. The electrostatic attraction and reduction on the adsorbents surface was considered to be the possible mechanism of Cr(vi ) removal. These studies revealed the potential application of MoS2 /rGO for Cr(vi ) removal.